Analisis Penegakan Disiplin Terhadap Warga Binaan Dalam Menajalani Masa Hukuman Di Rutan Klas I Tanjung Gusta Medan - Tarigan, Jeripan; Fikri, Rahul Ardian; Bintang, Hasdiana Juwita (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The implementation of the correctional system as a coaching system is essentially a multidimensional activity, because efforts to restore the unity of relationships are a very complex problem. Realizing that the development of correctional assisted residents based on the correctional system is an interactive activity between the inmate component, officers and the community, community participation is one of the absolute things that is absolutely necessary. The research was conducted in the city of Medan, precisely at the Class I Tanjung Gusta Detention Center (RUTAN) Medan. This study uses an empirical juridical approach method, the data obtained in the field is presented descriptively using the empirical normative approach method. This study is to find out the Analysis of Legal Arrangements in the Development of Correctional Assisted Citizens who commit violations of the rules of order in the Class I Tanjung Gusta Medan Detention House, Obstacles in the Implementation of Guidance for Correctional Assisted Residents Who Violate the Rules of Conduct in the Class I Tanjung Gusta Medan Detention House (RUTAN). Based on the results of the research obtained by the author, the implementation of legal arrangements in the development of correctional inmates who commit violations of order in the Class I Tanjung Gusta Medan Detention House (RUTAN) is a special prison police (polsuspas) based on the regulations of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 6 of 2013 which was updated to the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 29 2017 concerning the Rules of Conduct of Correctional Institutions and State Prisons and Law Number 22 of 2022 concerning Correctional Services to fulfill the rights of correctional inmates. The obstacle in the implementation of Coaching for Correctional Assisted Residents Who Violate Rules of Conduct at the Class I Tanjung Gusta Medan Detention Center (RUTAN) is if the prisoner has not received a verdict or incriminating verdict from the Court because he is still entrusted to the Tanjung Gusta Medan Class I Detention Center (RUTAN ) because it is still in the process of the investigation stages who are still in the custody of the Police and the Prosecutor's Office.